2008
DOI: 10.1021/ja8039794
|View full text |Cite
|
Sign up to set email alerts
|

Growth-Controlled Formation of Porous Coordination Polymer Particles

Abstract: Diversely shaped porous coordination polymer particles (CPPs) were synthesized by a simple solvothermal reaction of 1,4-benzenedicarboxylic acid (H2BDC) and In(NO3)3 x xH2O in DMF. The growth of crystalline CPPs was controlled through a particle growth blocking event involving blocking agent interaction with particular facets of CPPs and simultaneous particle growth interruption in a specific direction. Systematic reactions in the presence of various amounts of pyridine as a blocking agent were conducted to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
242
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(261 citation statements)
references
References 30 publications
(65 reference statements)
10
242
0
Order By: Relevance
“…[ 25 ] Therefore, adjusting the growth rates of different crystal facets should be applicable for the growth of low-dimensional MOFs, e.g., using growth-blocking agents to inhibit the crystal growth in certain directions. [ 26,27 ] As one of the most important MOFs, HKUST-1 (i.e., Cu 3 (BTC) 2 (H 2 O) 3 , where the parent molecule of BTC 3− linker is H 3 BTC (1,3,5-benzenetricarboxylic acid, see Scheme 1 )), has been widely studied since it was fi rst reported in 1999. [ 28 ] In this MOF, all three carboxyl groups in H 3 BTC molecule (through deprotonation) are coordinated with Cu 2+ ions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 ] Therefore, adjusting the growth rates of different crystal facets should be applicable for the growth of low-dimensional MOFs, e.g., using growth-blocking agents to inhibit the crystal growth in certain directions. [ 26,27 ] As one of the most important MOFs, HKUST-1 (i.e., Cu 3 (BTC) 2 (H 2 O) 3 , where the parent molecule of BTC 3− linker is H 3 BTC (1,3,5-benzenetricarboxylic acid, see Scheme 1 )), has been widely studied since it was fi rst reported in 1999. [ 28 ] In this MOF, all three carboxyl groups in H 3 BTC molecule (through deprotonation) are coordinated with Cu 2+ ions.…”
Section: Introductionmentioning
confidence: 99%
“…Oh et al [282] reported an inverse relationship between the amount of pyridine in the reaction and the length of nicely hexagonally shaped particles of [In(OH)(BDC)] n CPs, so that rods typically 16 µm long could decrease one order of magnitude, when either the capping agent was absent or in 25 equivalents, respectively. Interestingly, the dimensions of the hexagonal facet did not change regardless the concentration of pyridine, that is, the blocking effect affected selectively one growth direction.…”
mentioning
confidence: 99%
“…Other studies have also reported the inherent difficulties involved in determining the exact molecular structure of CPs. 16,17 Nevertheless, the band at 319 cm -1 in the Raman spectrum corresponds to the formation of Cd-O and Cd-S bonds; this confirms the extended coordination of the O and S atoms of MSA to the Cd(II) ion (Figure 1e). 18 The formation of the Cd thiolate complex indicates the possible conversion of the complex into CdS particles by calcination.…”
Section: Resultsmentioning
confidence: 53%